2015
DOI: 10.1021/nn507046h
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and in Vitro Antimicrobial Activity of Silver-Bearing Degradable Polymeric Nanoparticles of Polyphosphoester-block-Poly(l-lactide)

Abstract: The development of well-defined polymeric nanoparticles (NPs) as delivery carriers for antimicrobials targeting human infectious diseases requires rational design of the polymer template, an efficient synthetic approach and fundamental understanding of the developed NPs, e.g., drug loading/release, particle stability, and other characteristics. Herein, we developed and evaluated the in vitro antimicrobial activity of silver-bearing, fully biodegradable and functional polymeric NPs. A series of degradable polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 55 publications
3
70
0
Order By: Relevance
“…Interestingly, our group has recently reported a similar behavior for the hydrolytic degradation of a related carboxylate-functionalized PPE- b -PLLA copolymer upon incubation in buffered aqueous systems. 34 In the present case, the fast drop in surface charge (Figure 4B) would support the hypothesis that main chain scissions are occurring predominantly over side chain cleavage. In a seminal study, Baran and Penczek showed, using NMR spectroscopy and titration techniques, that incubation pH value exerts a profound influence on the relative rate of hydrolysis of main chain versus side groups in methoxy-substituted polyphosphoesters.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…Interestingly, our group has recently reported a similar behavior for the hydrolytic degradation of a related carboxylate-functionalized PPE- b -PLLA copolymer upon incubation in buffered aqueous systems. 34 In the present case, the fast drop in surface charge (Figure 4B) would support the hypothesis that main chain scissions are occurring predominantly over side chain cleavage. In a seminal study, Baran and Penczek showed, using NMR spectroscopy and titration techniques, that incubation pH value exerts a profound influence on the relative rate of hydrolysis of main chain versus side groups in methoxy-substituted polyphosphoesters.…”
Section: Resultssupporting
confidence: 82%
“…Despite the apparent similarity in behavior at both pH values, it should be noted that macroscopic precipitation was observed within 20 h upon incubation at pH = 7.4, whereas it took 5 d at pH = 5.0. The major effect exerted by the pH of the incubation medium over the kinetics of degradation of polyphosphoesters has been previously reported in the literature 34,37,3943 and is discussed further below, in light of the DLS data. At lower temperature (4 °C) the polyphosphoester backbone was substantially more stable at both pH values and most of the degradation that occurred was imputable to the fact that the NMR experiments were run at room temperature, which led to a faster apparent degradation.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…, Yersinia pestis ). Direct application to the bladder luminal surface of nanoparticles, perhaps coated with the FimH adhesin [85], has also been explored in mice as a means to accomplish targeted delivery of novel therapeutics to the host [86]. …”
Section: Next-generation Therapeuticsmentioning
confidence: 99%